(untitled) (Comillas Journal of International Relations, 2020)
Climate Change is the the world’s greatest threat of our time and we are at a defining moment. In addition, we are very close to one of the worst economic and social crisis ever, because of COVID-19. Within this frame, it is an urgent issue to implement the 2030 Agenda at all educational levels, with the aim of achieving the 17 Sustainable Development Goals. School gardens and school agroecology are fundamental tools to develope gobal citizenship education and implement the SDG at schools. This article is a review of some national proposals and reflections.